Moringa oleifera Linn: Extraction, Phytochemistry Constituent and Pharmacology Activity: A Review - Yamin Yamin; Ruslin Ruslin; Ratna Asmah Susidarti; Abdul Rohman (Faculty of Pharmacy, Universitas Gadjah Mada, 2025)
Moringa oleifera, commonly known as the “miracle tree”, belongs to the Moringaceae family and is a plant that has functional food and nutraceutical properties. Various parts of this plant are rich sources of carbohydrates, proteins, amino acids, lipids, vitamins, polyphenols and minerals. This review is a comprehensive summary of the extraction method, phytoconstituents, traditional uses, and pharmacological activity of this plant, namely as an antioxidant, antimicrobial and antifungal, anti-inflammatory, anti-diabetic and anti-obesity, antiviral. This is because Moringa leaves contain flavonoids and phenolics. In addition, Moringa leaves contain a large number of phytochemicals which are excellent for the development of functional products applied in various industries including pharmaceutical, cosmetic, nutraceutical and food.